Worker injuries involving the interaction of cattle, cattle handlers, and farm structures or equipment - Fox, Shannon L. (Kansas State University, 2011)
Cattle and other livestock have been identified as leading sources of injuries to workers in agriculture. Cattle handling injuries can be serious and often appear to be under-reported [superscript]3,[superscript]4. Many of these injuries involve predictable patterns of interactions among victims, animals, and fixed farmstead structures or gates. There has been some progress toward developing safer facility designs and work procedures, but continuing reports of injuries suggest further efforts are still needed. The present study focused on worker injuries that involved the interaction of three elements: (a) cattle, (b) cattle handlers, and (c) farm structures or equipment—including swinging gates and stationary barriers. The goal of the study was to identify opportunities for injury prevention. The source of injury cases was the Consumer Product Safety Commission’s National Electronic Injury Surveillance System (NEISS)[superscript]29,[superscript]45. We believe this is the first report of cattle related injuries based on NEISS data. We selected the NEISS database for this investigation because it includes product codes for many farmstead barriers such as fences, walls, and doors. The database was also selected because it contains brief narratives that help to describe the circumstances of each incident. Predictable interactions between humans, animals, and farm structures led to many of the cattle handling injuries reported in the NEISS database. In almost 30% of cases, cattle pushed workers into structures such as fences, gates, posts, and walls. In another 16-19% of injuries, cattle struck gates and other objects, propelling them at the victims. These percentages are similar to findings reported in previous studies that drew on data from New York hospitals[superscript]10, news reports in the central United States[superscript]5, and workers compensation cases in Colorado[superscript]3,[superscript]4. In all, gates and other physical barriers contributed to about 45% of cattle handling injuries in the present study.
Keywords: Cattle; Safety; Injuries; Agriculture, General (0473); Animal Sciences (0475)